The Effect of Transformational Leadership and Organizational Climate on Employee Performance Through Organizational Commitment as an Intervening Variable - Irwan Sani (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the influence of transformational leadership and organizational climate on employee performance through organizational commitment. The method used is a quantitative descriptive method. The research results show that transformational leadership and organizational climate have a positive and significant influence on organizational performance, both directly and through organizational commitment. The conclusion is that the role of transformative leadership and a conducive organizational climate is important in improving employee performance through a high level of organizational commitment. Keywords: Employee Performance, Organizational Climate, Transformational Leadership, Organizational Commitment